Kedudukan Hukum Video Game Dalam Sistem Hukum Positif Di Indonesia - Sinaga, Jaya Setiawan; Silubun, Yosman Leonard (Universitas Musamus, 2025)
The rapid growth of the video game industry in Indonesia has transformed the sector from mere entertainment into a significant pillar of the national creative economy. However, the complexity of its internal elements creates juridical challenges regarding how Indonesian positive law provides comprehensive protection. This study aims to analyze the legal standing of video games as multimedia creations within the copyright system and to examine the legal protection of virtual assets and their administrative governance in Indonesia. The research method employed is normative judicial with statutory and conceptual approaches. The results indicate that video games are recognized as independent creations under Article 40 paragraph (1) letter r of Law Number 28 of 2014; however, technically, they constitute multimedia works with multilayered protection encompassing computer code, fine arts, audio, and narratives. From a civil law perspective, virtual assets and game accounts are classified as intangible movable objects possessing real economic value, thereby entitling them to protection against data theft under the Law on Electronic Information and Transactions (UU ITE) and the Personal Data Protection Law (UU PDP). Furthermore, the state exercises administrative intervention through the Indonesia Game Rating System (IGRS) for content classification and the recognition of esports as a performance sport, which mandates the institutionalization of legal entities. The study concludes that video game protection in Indonesia has been integrated through various legal regamees—intellectual property rights, civil law, and administrative regulations—to ensure legal certainty for developers and protection for consumers within the digital ecosystem.